Changes of lipofuscin-like pigments in erythrocytes and spleen after whole-body gamma irradiation of rats - Wilhelm, J; Brzák, P; Rejholcová, M (Radiation research, 1989)
Whole-body gamma irradiation of rats induced the formation of lipofuscin-like pigments in erythrocytes. Erythrocytes that were damaged by oxidation were scavenged in the spleen, and lipofuscin-like pigments were transferred from erythrocytes to the spleen during this process. The time course of lipofuscin-like pigments in erythrocytes and spleen indicates that the pigments were not induced by the action of free radicals produced by ionizing radiation but rather were a sequela of postirradiation metabolic changes.
Keywords: inbrední kmeny potkanů; Gamma Rays; Lipofuscin; Erythrocytes; Rats, Inbred Strains; krysa rodu Rattus; záření gama; Biomarkers; zvířata; biologické pigmenty; Whole-Body Irradiation; lipofuscin; Pigments, Biological; Cobalt Radioisotopes; biologické markery; Male; celotělové ozáření; Spleen; erytrocyty; Rats; Animals; radioizotopy kobaltu; mužské pohlaví; slezina